Mesenchymale Tumoren des Mediastinums = Mesenchymal tumors of the mediastinum - Rieker, Ralf Joachim; Marx, Alexander (Der Pathologe, 2016)
Mesenchymal neoplasms of the thymus and mediastinum account for only 2 % of neoplasms of the mediastinum and are therefore very rare. With very few exceptions the histology, immunohistochemistry and (based on current knowledge) molecular biology of mediastinal soft tissue tumors are not different from their counterparts in other organs. Characteristic features are more concerned with clinical epidemiological and therapeutic aspects as well as the multitude of possible differential diagnoses. With the exception of organ-specific tumors, such as gastrointestinal stromal tumors (GIST), virtually all entities encountered in peripheral soft tissues can also arise in the mediastinum. Primary mediastinal soft tissue sarcomas (STS) must be distinguished from secondary radiation-induced STS after irradiation, e. g. for breast cancer and Hodgkin’s lymphoma and from STS arising as somatic type malignancies in mediastinal germ cell tumors